Diagnóstico de la situación financiera de la empresa Proyectar Diseños y planteamiento de las estrategias financieras para los próximos siete años (2022)
TThe present investigation analyzes the financial behavior of the company Proyectar Diseños in the last seven years to determine the strategies that improve its financial management, increase its profitability and mitigate possible financial problems that result after the COVID-19 pandemic. For which, the collected information is analyzed in a mixed method, including quantitative and qualitative variables in the diagnosis of financial statements, using vertical and horizontal analysis, liquidity, indebtedness, activity and performance indicators. In addition, a survey is developed to identify the liquidity and profitability situations of the company that proceed to establish financial strategies focused on improving these indicators based on recommended estimates in current assets, production costs and contribution margins. Next, based on these analyses, the financial statements are projected for the next seven years, calculating the Net Present Value (NPV) and the Internal Rate of Return (IRR), obtaining the flows of expenses and income in a positive value on the basis of the initial year and the corrections that are suggested in the management of short-term assets and liabilities. In conclusion, the company with these projections could achieve a profitable contribution margin in a short and long-term sustainability standard of the assets involved by the owners and partners of the company. It is important to highlight that the company at the beginning of the investigation had a net profit margin of less than 1%, which in hindsight implied a rate of return close to zero, so it is concluded that the recommendation is to mainly maintain control over the current assets and liabilities, making strategic alliances with suppliers that allow it to extend the terms and reduce the value paid for inventories